Interactive Multimedia Educational Games Science Module / Kew Yen Hoon - Kew, Yen Hoon (2003)
For the past three months my partner and I has studied the design and use of educational games for mathematics and science education in ages 9 to 12. Our research about "Interactive Multimedia Educational Games" has involved lecturers and course mates in Faculty computer science and information technology, teachers and some of the children. The outcomes of this collaboration will be included a wide range of research studies as what we had done. Efforts are put to ensure that games can be very effective in increasing both motivation and achievement in mathematics and science learning. The thesis title was chosen as "Interactive Multimedia Educational Game" because of their appeal to children and because they offer excellent opportunities for visualization and exploration of some concepts. I will develop the educational games for Science module while my partner will develop the Mathematics module. One of the objectives of this game is to help teachers in teaching Science in English and to help the students to understand the subject more effectiveness. Lastly, I do hope this "Interactive Multimedia Educational Games" were effective in enhancing mathematics and science learning for purposes beyond memorization drills. Also, can serve to enable children enjoy themselves throughout the playing and learning process, and to achieve the specified objectives.